2021
DOI: 10.15537/smj.2021.42.11.20210529
|View full text |Cite
|
Sign up to set email alerts
|

Normative data of olfactory abilities using cultural adaption Sniffin’ sticks smell test in different age groups

Abstract: Objectives: To assess olfactory abilities using a culturally adapted Sniffin’ Sticks smell test in different age groups. Methods: This was a cross-sectional study, conducted at Otorhinolaryngology outpatient clinic of Universiti Kebangsaan Malaysia Medical Centre, Secondary Science School, and Children Learning Centre in Kuala Lumpur, Malaysia, from August 2019 until December 2021. Results: In 450 healthy participants, the cut-off points of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…There have been conflicting findings from studies evaluating the relation between age and olfactory performance. While several studies reported decreased olfactory ability in age groups over 55 years [16] , [24] , [25] , one study conducted in Malaysia revealed a different result whereby middle-aged adults (41–60 years) identified odors better than other age groups [20] . Evidence suggests that age-related olfactory impairments arise from a multitude of factors, such as anatomical and physiological changes, loss of selectivity of receptor cells to odorants, and changes in neurotransmitter and neuromodulator systems [26] , [27] .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…There have been conflicting findings from studies evaluating the relation between age and olfactory performance. While several studies reported decreased olfactory ability in age groups over 55 years [16] , [24] , [25] , one study conducted in Malaysia revealed a different result whereby middle-aged adults (41–60 years) identified odors better than other age groups [20] . Evidence suggests that age-related olfactory impairments arise from a multitude of factors, such as anatomical and physiological changes, loss of selectivity of receptor cells to odorants, and changes in neurotransmitter and neuromodulator systems [26] , [27] .…”
Section: Discussionmentioning
confidence: 95%
“…Normative data of the VSIT scores were recorded as means, standard deviations (SDs), medians, ranges, and percentiles, stratified for sex and age groups. The 10th percentile values in each age group and each sex were established to separate the normosmic from the hyposmic subjects [16] , [20] , [21] . Percentile ranks for olfactory function by age group and sex were also described.…”
Section: Methodsmentioning
confidence: 99%
“…12 Hence, consenting participants were screened for smell impairment with a validated culturally adapted Malaysian version of the Sniffin’ Sticks smell identification test with 16 types of odours. 12,13 The tip of each pen with its own odour was placed approximately 2 cm in front of the nostrils for approximately 3 seconds. The participants thereby identified the odorant from a list of four items (including one correct answer and three distractors).…”
Section: Methodsmentioning
confidence: 99%
“…Cultural background tends to affect olfactory performance. 12 Hence, consenting participants were screened for smell impairment with a validated culturally adapted Malaysian version of the Sniffin' Sticks smell identification test with 16 types of odours. 12,13 The tip of each pen with its own odour was placed approximately 2 cm in front of the nostrils for approximately 3 seconds.…”
Section: Cultural Adaptation Of the Sniffin' Stick Smell Testmentioning
confidence: 99%
“…Olfaction is an important sense that can regulate emotions, affects cognition and behavior (Liu et al, 2020 ; Zambom-Ferraresi et al, 2021 ), and also reminds us of dangers in the environment (Husain et al, 2021 ). It can be impaired by chronic rhinosinusitis, head trauma, infections, aging, long-term smoking, alcoholism, metabolic diseases, and autoimmune diseases (Topan et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%